Medical cannabis for treatment-resistant combat PTSD - Nacasch, Nitsa; Avni, Chen; Toren, Paz (Frontiers in Psychiatry, 2023)
Targeting the endocannabinoid system may have a role in the treatment of post-traumatic stress disorder (PTSD).. However, few studies have examined the effectiveness of cannabis on symptoms of PTSD, and more research is needed to ascertain cannabis' effectiveness. In this retrospective naturalistic study, we followed 14 relatively mature (32-68 years of age), treatment-resistant, chronic combat post-traumatic patients who remained severely symptomatic despite treatment with many lines of conventional treatment prior to receiving medicinal cannabis. Our findings show an overall improvement in sleep quality and duration as well as a decrease in other symptoms by at least 20% in over 65% of patients, with nearly 80% of patients showing improvement. Unlike some other studies, the decrease in nightmares was observed but was not statistically significant.